2020
DOI: 10.1002/btpr.3098
|View full text |Cite
|
Sign up to set email alerts
|

Using microalgae for remediation of crude petroleum oil–water emulsions

Abstract: Crude petroleum oil spills are among the most important organic contaminations.While the separated oils accumulated on the surface water are relatively easily removed, the emulsified portions are more difficult to remove and pose significant threats to the environment. Bioremediation using bacteria has proven to be an effective method, but the biomass produced in this case does not have any significant remunerative value. In this work, microalgae were proposed to combine emulsified oil remediation process with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It has been reported that some species can significantly reduce aliphatic compounds, such as 3-methyl decane, heptadecane, and octadecane [16], and that the ability of Chlorella spp. to reduce emulsified oil reached 80 % [17]. Further studies have shown that Chlorella spp.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some species can significantly reduce aliphatic compounds, such as 3-methyl decane, heptadecane, and octadecane [16], and that the ability of Chlorella spp. to reduce emulsified oil reached 80 % [17]. Further studies have shown that Chlorella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorella vulgaris was tested in a study and was grown at altered temperature and in different concentration of emulsified oil. Results shows an increase in specific growth rate and decrease in drop oil concentration (Kuttiyathil et al 2021).…”
Section: Introductionmentioning
confidence: 91%
“…but also how, in nature, the mechanical action of sea waves contributes to creating an emulsion of water and crude oil that could favour the removal of pollutants making them more available. Their results show that following an initial period of adaptation, the Total Organic Carbon (TOC) of the solution was drastically reduced and that, after 5 days, Chlorella removed 80% of the emulsified oil [35]. Water mixing and how it can alter bioremediation was also studied in 2014 by Özhan et al, which demonstrated how the bioavailability of crude oil is altered by physical mixing applied in the laboratory.…”
Section: Microalgae and Petroleum Bioremediationmentioning
confidence: 99%
“…The hormesis hypothesis claims that an organism responds to small doses of stress adaptively to survive [50]. However, some studies show that the ability of microalgae to remove contaminants continues even after the cell is dead as the microalgae can adsorb micro-drops of crude oil on their surface and, consequently, TOC, removing it from the solution as demonstrated by Kuttiyathil et al [35].…”
Section: Mechanism Of Actionmentioning
confidence: 99%